Designing a VTuber Character for Institutional Image Communication: A Case Study of ‘Notto’ at the Faculty of Information Technology and Digital Innovation, North Bangkok University.” - ยศบุญเรือง ศุภกิตติ์; ดาวเรือง นฤเดช; ดีเจริญชิตพงศ์ จิรวิญญ์; เขื่อนแก้ว ปรานต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled “VTuber Character Design for Image Communication: A Case Study of ‘Notto,’ Faculty of Information Technology and Digital Innovation, North Bangkok University,” aims to study the design and development process of the VTuber character “Notto.” The name “Notto” is derived from the abbreviation and phonetic transformation of the word “North,” making it shorter, concise, and easy to remember, particularly suitable for a younger audience. A Japanese-style suffix is added to align with VTuber culture. The character design incorporates blue and white, which are the official colors of North Bangkok University, as the primary color scheme. Additionally, the logo of the Faculty of Information Technology and Digital Innovation is placed on the character’s costume to enhance recognition and establish a clear identity. The overall purpose is to create a modern image and attract interest toward the Faculty of Information Technology and Digital Innovation at North Bangkok University The study also aims to disseminate the work through YouTube and the public relations media of the Faculty of Information Technology and Digital Innovation, as well as to evaluate audience satisfaction and generate interest among viewers. The sample group consisted of 30 participants selected using convenience sampling from students at North Bangkok University. The results of the study revealed that the overall mean score for content quality evaluation by content experts was 3.46 with a standard deviation (S.D. = 0.50), which was interpreted as a moderate level of quality. The overall mean score for media quality evaluation by media experts was 3.91 with a standard deviation (S.D. = 1.13), which was interpreted as a high level of quality. The satisfaction evaluation of students at North Bangkok University who viewed the VTuber character design yielded a mean score of 3.46 with a standard deviation (S.D. = 0.50), which was interpreted as a moderate level of satisfaction.